Development of Web-prototype for analysis of statements in social network Twitter - Glybovets, A.M.; Hontar, M.A. (PROBLEMS IN PROGRAMMING, 2019)
This article describes a software prototype for statistical analysis of expression in social networks with previous filtration of non-information expressions, selection of characteristic words, naive Bayesian classifier for providing analysis of user statements.